AB0185 Undercarboxylated Osteocalcin as A Marker for Metabolic Dysfunction in Patients with Rheumatoid Arthritis. (15th July 2016) - Lee, E.-J.; Ghang, B.; Lim, D.-H.; Hong, S.; Lee, C.-K.; Yoo, B.; Kim, Y.-G.
Abstract : Background: Osteocalcin (OC) has been known as one of bone-forming markers and the serum level in rheumatoid arthritis (RA) patients was usually lower than that in healthy control. Serum OC, secreted from osteoblasts, exists in either carboxylated OC (cOC, major form) or undercarboxylated OC (ucOC, minor form). Different to the osteogenic role of cOC, ucOC has been suggested to be involved in energy metabolism. Recent studies have shown that significantly lower concentration of ucOC in the blood was associated with metabolic derangement including insulin resistance. Therefore, we would like to investigate whether level of ucOC in RA patients decreased and it was accompanied by metabolic dysregulation, which has never been studied before. Objectives: To determine the association between ucOC and metabolic alteration including insulin resistance in patients with RA Methods: Clinical information of patients and healthy volunteers was collected from electronic data base of single center registry. The concentrations of cOC and ucOC were measured in the sera from established RA patients (n=30) and healthy subjects (n=13) by enzyme-linked immunosorbent assay (ELISA). Various metabolic parameters, including insulin concentration, homeostasis model assessment of insulin resistance (HOMA-IR) and body mass index (BMI), were measured and analyzed. Results: The concentration of cOC in blood was not significantly different between RA patients (13.49±2.97 ng/mL) and healthy controls (14.45±2.48 ng/mL). However, the concentration of ucOC was significantly lower in the sera of patients with RA (3.29±2.36 ng/mL) than in those of healthy individuals (5.94±2.75 ng/mL, p =0.003). Intriguingly, ucOC levels have been found to be positively associated with parameters of metabolic derangement including insulin levels, HOMA-IR and BMI (Figure 1 ). These associations were not found in healthy controls. Conclusions: The present study show that the concentration of ucOC, but not cOC was significantly lower in patients with RA, and its value was positively correlated with insulin resistance. Therefore, ucOC can be supposed to have a unique role in metabolic dysregulation in RA. Disclosure of Interest: None declared